Finance reform under local integration - S. S. Seryohin (Aspekti Publìčnogo Upravlìnnâ, 2016)
Abstract Revealed the essence of local finance manifested in economic relations, and their structure is a combination of local budgets, special purpose budget funds; budget funds of local governments; public funds of funds banks if their share capital formed at the expense of local governments; fund municipal enterprises, institutions and organizations. The analysis on fundamental scientific research on local budgets.Defined-purpose local governments.Systematized theoretical definition of municipal finances. Formed impact of reform of local finance to ensure the improvement of socio-economic status of the region to the European Union for more confident of Ukraine’s integration into Europe. Found that implementing fiscal policy in terms of spending, local authorities are guided by the priorities of socio-economic development of the region or administrative unit in line with national principles defined government policy document. Discovered topical issues of local budgets as the existence of significant differences in the regulatory and legislative framework - the excessive centralization of local budgets unstable sources of local revenues inadequacy of intergovernmental relations. It was found that to radically change the existing system of functioning of local budgets, as required considerable time gap and improving the theoretical and methodological and regulatory framework of the local budgets.